A Model to Choose Hub and Route Determination - Kevin Kevin; Y. M. Kinley Aritonang; Julius Dharma Lesmono (Department Industrial Engineering, University of Muhammadiyah Malang, 2019)
Determining a transport hub is a strategic decision to build a good distribution flow. In this paper, We suggested a model for choosing hub locations as sources for companies. In previous studies, The determination of hub locations with a vehicle routing problem is not integrated. Therefore, this study built a model to assess the position of the hubs by considering the budget. The business should have a decision on vehicle routing with hubs to reduce total transport costs. In addition, the method of distribution of goods for hubs and non-hubs with third-party logistics was determined by the use of a vehicle routing problem. The optimal weight was obtained through the analysis of sensitivity. In the sensitivity analysis, this study found that the best choice in this study was to use a weight of 0.9–1.0. It provides the lowest total cost of transport.